EFFECTIVE FOOD GARDENS IN PRIMARY SCHOOLS - Hayes, Katy (My University, 2011)
South Africa is a food secure nation in terms of food availability but there are many food insecure families who are unable to access food on a daily basis. As a result children go to school hungry which impacts on their ability to learn. Food gardens have been identified as one of the ways in which to address these challenges but they are not always successfully implemented. The purpose of this qualitative study was to reveal what factors contributed toward the effective implementation of food gardens in primary schools. The findings indicate that stakeholder involvement, Principal support, motivation, passionate project leaders and focused objectives contribute towards successful gardens. In addition the use of sustainable gardening techniques and using the garden as a multiple resource are necessary for successful food gardening. The study also found that food gardens can be used to supplement school feeding schemes and to create learning opportunities
MM - P&DM
Keywords: Primary schools; Food gardens; Feeding schemes